Avaliação crítica dos parâmetros atuais de classificação da anemia dos fetos de gestantes aloimunizadas - Tiago Lanfernini Ricardo Coelho (2011)
The Fetal anemia, although rare, is considered an associated condition to a high perinatal morbidity and mortality, and main cause is maternal-fetal alloimmunization. Currently, there are different recommendations for the diagnosis and classification, whose statistics has not been studied. Objectives:Comparatively analyze the current diagnosis parameters and fetal anemia classification, highlighting their disagreements. Discuss and point out the most appropriate criteria for the severe anemicfetuses, based on perinatal evolution. Methodology:A retrospective study of Rh alloimmunization pregnant women, whose fetuses had cordocentesis applied because they present a utero anemia risk, in a referenced university service, between 1999 to 2009. Were evaluated the medical records, and selected those with reliable hemoglobin concentration rates and gestational age. The degreeof agreement in the diagnosis of severe anemia, from the three recommended criteria, was analyzed by Cohen's Kappa rate. Were evaluated the differences between the perinatal results between groups of agreement / disagreement in the classification of severe fetal anemia through usingthe Kruskall-Wallis test and chi-square Pearson'stest. Results: There was an agreed higher rate in the anemia diagnosis (kappa 0.80) when comparing the criteria proposed by Nicolaides et al.(1988) and Mari et al.2000. It was observed that all fetuses considered severely anemic by Mari et al. (2000) (30) were also considered by Bahado Singh et al. (1998). Evaluating from integrated way the three proposed recommendations for diagnosis and classification offetal anemia and compared with the perinatal outcome, was observed that the presence of fetal hydrops (p <0.001) and perinatal mortality (p <0.001) were statistically different between the groups analyzed, being therefore relevant for comparison among them. Among the three recommendations, we believe that the most conservative of them, proposed by Bahado-Singh et al. in 1998 is, so far, the most appropriate one since it includes all cases between the three different recommendations. Conclusions:The current diagnosis criteria indicate disagreement in the fetal anemia detection, as well as its severe form classification. In this last one, there are major differences, with a potential to change the perinatal result in terms of mortality and hydropsy occurrence. The 5 g cutoff point for fetal hemoglobin deficit, compared to the expected for a certain gestational age presents advantages in identifying a greater number of fetuses with high morbidity and mortality in relation to other proposals